2015
DOI: 10.1371/journal.pone.0118146
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi Sensu Lato Spirochetes in Wild Birds in Northwestern California: Associations with Ecological Factors, Bird Behavior and Tick Infestation

Abstract: Although Borrelia burgdorferi sensu lato (s.l.) are found in a great diversity of vertebrates, most studies in North America have focused on the role of mammals as spirochete reservoir hosts. We investigated the roles of birds as hosts for subadult Ixodes pacificus ticks and potential reservoirs of the Lyme disease spirochete B. burgdorferi sensu stricto (s.s.) in northwestern California. Overall, 623 birds representing 53 species yielded 284 I. pacificus larvae and nymphs. We used generalized linear models an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 80 publications
4
59
3
1
Order By: Relevance
“…We found that ground-foraging birds were more likely to be infested with ticks than those that forage elsewhere, a finding that is congruent with many other studies over different geographic regions (e.g., 7,70,71) and that reflects the ground-level hostseeking behavior of ticks (14). We also found that birds with reduced fat stores were more likely to harbor ticks.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that ground-foraging birds were more likely to be infested with ticks than those that forage elsewhere, a finding that is congruent with many other studies over different geographic regions (e.g., 7,70,71) and that reflects the ground-level hostseeking behavior of ticks (14). We also found that birds with reduced fat stores were more likely to harbor ticks.…”
Section: Discussionsupporting
confidence: 91%
“…Testing for B. burgdorferi in our study was not performed to identify vectors but rather to potentially learn about enzootic maintenance of the pathogen in local or migratory birds and their ticks, given that spirochetes in the avian blood could have been detected by our approach of testing the blood directly or testing the engorged ticks. Birds play a key role in the ecology of Lyme disease through contributing to the range expansion of ticks and maintaining B. burgdorferi in the environment in areas where Lyme disease is recognized as endemic or emerging (4,26,(68)(69)(70). Regional studies of pathogen prevalence are increasingly important from ecological and human health perspectives, especially considering that the annual movement patterns of many of the birds connect geographic zones in which Lyme disease is endemic with those in which it is nonendemic.…”
Section: Discussionmentioning
confidence: 99%
“…range expansion will also be affected by available host habitat or host movement, which was not explicitly included in our models. Although the expansion in the distribution of I. scapula-ris ticks is driven in large part by the movement of white-tailed deer (Rand et al 2003), the primary host of the adult life stage of the tick, others have pointed to the potential role of migratory birds in B. burgdorferi transmission dynamics through the introduction of infected larvae and nymphs to areas without established I. scapularis populations or with only pathogenically naïve tick populations (Scott et al 2001, Brinkerhoff et al 2011, Newman et al 2015). Future tick surveillance and modeling efforts could target riparian corridors or known migration routes that could be a factor in the long-range dispersal of ticks (Weisbrod and Johnson 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Eastern fence lizards ( Sceloporus undulates ) and five-lined skinks ( Eumeces fasciatus ) in the eastern United States are inefficient reservoirs either because they infect few ticks or because they carry few ticks even if they are capable of transmitting B. burgdorferi (Levin et al 1996, Giery and Ostfeld 2007, Rulison et al 2014). Birds vary widely in their competency as effective reservoir hosts (Mather et al 1989a, Magnarelli et al 1992, Ginsberg et al 2005, Newman et al 2015). …”
Section: Enzootic B Burgdorferi Transmission In the United States Anmentioning
confidence: 99%